THE IMPACT OF SERVICE QUALITY, FACILITY, PRICE, EMOTIONAL FACTOR AND LOCATION ON CUSTOMER SATISFACTION AND LOYALTY AT THE 3-STAR HOTELS IN BEKASI - Kumar, Suresh; Winarto, Budi; Astuti, Mariana (Buletin Studi Ekonomi; VOL.20.NO.1.FEBRUARI 2015 (PP 1-82), 2016)
The Impact Of Service Quality, Facility, Price, Emotional Factor and Location On Customer Satisfaction And Loyalty At The 3-Star Hotels In Bekasi. Hospitality business is one of the industries that has the greatest impact at which foreign companies are entering, namely telecommunications, air transportations, bankings, hotels, etc. To stay in competition, customer satisfaction must be fulfilled by hoteliers. In order to do that, service quality can be one of the factors to determine satisfaction. Other than service quality, facility, location, emotions, price also play a significant influence on satisafaction which lead to loyalty. Construct validity is checked through correlation and found that the variables were loaded on its respected factor, and reliability result shows higher than 0.7. Service quality was rejected since the results showed negative sign. Factors like facility, location, price and emotions show significant influence on customer satisfaction and customer satisfaction influneces loyalty. Hotel managers can focus on these factors to stay in the competition. Keywords : consumer satisfaction, loyalty, service quality, price, facility, emotional factor, location
Keywords: consumer satisfaction, loyalty, service quality, price, facility, emotional factor, location